2017
DOI: 10.1177/0018720817701000
|View full text |Cite
|
Sign up to set email alerts
|

Head Rotation Movement Times

Abstract: The data of this study add to those in the review of Hoffmann for the critical IDs of different body motions. The data also allow design for the best arrangement of display that is under the design constraints of limited display area and difficulty of head-controlled movements in a data-inputting task.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…We used the logarithmic rule to describe the relationship with MT for object size, target tolerance, and movement amplitude in our model, but some other studies have used the square root function to describe these relationships (Chen et al, 2015; Hoffmann, Chan, & Heung, 2017; Lin & Drury, 2011). Both functions have been used in previous studies and can explain the effect of movement amplitude and target width very well.…”
Section: Discussionmentioning
confidence: 99%
“…We used the logarithmic rule to describe the relationship with MT for object size, target tolerance, and movement amplitude in our model, but some other studies have used the square root function to describe these relationships (Chen et al, 2015; Hoffmann, Chan, & Heung, 2017; Lin & Drury, 2011). Both functions have been used in previous studies and can explain the effect of movement amplitude and target width very well.…”
Section: Discussionmentioning
confidence: 99%
“…This movement pattern can be described in two phases: (1) the initial movement, described by high velocity and imprecise change in position toward a target position; and (2) the final movement, which is slower, but more precise than the initial movement ( Fitts, 1954 ; Chen et al, 2012 ). Demonstrating the efficacy of this model with regards to head movement ( Hoffmann et al, 2017 ) observed that the time of movement along the yaw axis increased as the difficulty of target acquisition increased (via manipulation of target size), showing that head movements of 60° required 550 ms (109°/s) for the easiest targets, and 900 ms (66.7°/s) in the most difficult targets.…”
Section: Physical Properties Of Head Movementmentioning
confidence: 99%
“…It is the time required for a user to complete a movement using one of their body segments. Examples of such movements include finger movements in small amplitude tapping tasks [1], hand/arm movements with an object to transfer the location of the object or tap a target with/without a stylus [2][3][4][5][6][7][8][9], foot movements to push a pedal or tap a target [10][11][12][13][14], head movements to give a command to a computer or other device [15][16][17][18][19], trunk movements to support the upper extremity movements or to indicate the functional capability of the body [20,21], and so on. Fitts' law [2,3] is probably the most commonly adopted scientific basis for explaining the MT of a body segment.…”
Section: Introductionmentioning
confidence: 99%